A novel chemically defined serum‐ and feeder‐free medium for undifferentiated growth of porcine pluripotent stem cells. Issue 9 (30th January 2019) - Zhang, Xue; Xue, Binghua; Li, Yan; Wei, Renyue; Yu, Zhuoran; Jin, Junxue; Zhang, Yu; Liu, Zhonghua
Abstract: Development and improvement of in vitro culture system supporting self‐renewal and unlimited proliferation of porcine pluripotent stem cells (pPSCs) is an indispensable process for the naïve pPSCs establishment. In this study, we modified the previous culture system and attempted to develop a novel chemically defined medium (KOFL) for the establishment of pPSCs. It has been cultured >45 passages with flat colony morphology and normal karyotypes in in vitro environment. These cells exhibited alkaline phosphatase activity and expressed pluripotency markers such as OCT4, SOX2, and NANOG, and also possessed differentiation abilities both in vitro and in vivo, proving by the formation of embryonic bodies and teratomas into three germ layers. Then the cells transfected with a green fluorescent protein (GFP) and the GFP positive cells contribute to the porcine preimplantation embryo development. In addition, these cells maintained long duration under feeder‐free condition. In conclusion, our results demonstrated that the pPSCs could be derived from preimplantation porcine embryos in serum‐free medium and cultured under the feeder‐free condition, providing an effective reference for further optimization of the pPSCs culture system. Abstract : These results demonstrated that the porcine pluripotent stem cells (pPSCs) could be derived from preimplantation porcine embryos in serum‐free medium and cultured under the feeder‐free condition, providing an effective reference for further optimization of the pPSCs culture system.